Associations Between Weight‐Based Bullying, Developmental Internal Assets, and Perceived Social Support Among Youth. (16th November 2021) - Yourell, Jacqlyn L.; Doty, Jennifer L.
ABSTRACT: BACKGROUND: Youth with obesity are likely to experience weight‐based bullying victimization, and adolescents have the highest obesity rates among children. Factors that protect youth from traditional bullying victimization may protect youth from weight‐based bullying victimization: internal assets such as positive identity and social competence, and external assets such as perceived support from parents and friends. METHODS: To examine this proposition, data from 8th, 9th, and 11th graders were obtained from the 2016 Minnesota Student Survey (N = 126, 495). Logistic regressions were conducted to identify the relationship between assets and weight‐based bullying and to determine possible moderation by weight status. RESULTS: Results demonstrate that positive identity, parent support, and friend support were associated with lower odds of experiencing weight‐based bullying victimization. Moderation analyses revealed that perceived parent support was most protective against experiencing weight‐based bullying victimization among youth with obesity compared to youth with overweight, normal weight, or underweight. CONCLUSION: School administrators, counselors, and teachers should be aware of the increased risk of weight‐based bullying for youth with obesity and underweight. Results underscore the need to foster youth's internal assets like positive identity to promote a strength‐based approach for prevention. Parent involvement is warranted in weight‐based bullying prevention efforts.